MULTIMEDIA BASED SYSTEM FOR ‘AYURVEDA’ MEDICINE FOR THE NEXT GENERATION - Perera, Rishni; Dias, G.K.A. (International Journal of Research -GRANTHAALAYAH, 2017)
Traditional systems of medicines, including herbal medicines, have been used for many centuries for health care by people in South East Asia as well as in other parts of the world. Traditional medicine or Ayurveda medicine continues to be a valuable source of remedies that have been used by millions of people around the world to secure their health. Sri Lankan Ayurveda has long history and is a popular medical system in Sri Lanka. Our present generation lacks the knowledge in medicinal plants based herbal drugs as well as indigenous medicine or Ayurveda natural home remedy medicine like previous generation. Our main motivation is to save this valuable indigenous medicine system we develop for the next generation. The main features of the system are search facility, plant dictionary, video gallery including 3D animation, virtual tour and a report generator. The system CeylonHerb will bring indigenous medicine system to digital world as a multimedia based multilingual application.